LITERATUR RIVIEW: PENGARUH PENDIDIKAN KEWIRAUSAHAAN DAN NORMA SUBJEKTIF TERHADAP INTENSI BERWIRAUSAHA - Marcelina, Sherly; Kurniawan, Riza Yonisa (Jurnal Pendidikan Ekonomi (JURKAMI), 2024)
Students who have doubts about becoming an entrepreneur are the basis for this research. This research is also based on other research that many students who have received entrepreneurship education at university level but still feel hesitant about becoming an entrepreneur. Therefore, this research is considered important to carry out to strengthen this argument, so a literature review is considered appropriate. The literature review conducted was to determine that entrepreneurial intention can be influenced by entrepreneurial education factors and subjective norms implemented through the research method, namely SLR or Systematic Literature Review. Based on the study conducted, it shows that entrepreneurial intention is significantly influenced by entrepreneurial education and subjective norms. The results of the literature review also found that entrepreneurial education and subjective norms have an impact on entrepreneurial intention, so that entrepreneurial education and subjective norms can be implemented as a strategy to increase individual entrepreneurial intention. Thus, it is very crucial for the government and educational institutions to encourage increased entrepreneurship education so that individual entrepreneurial intention increases.